Idolatry and its enemies : colonial Andean religion and extirpation, 1640-1750 - Mills, Kenneth, 1964- (Princeton University Press, 1997)
The ecclesiastical investigations into Indian religious error - the Extirpation of idolatry - that occurred in the seventeenth- and eighteenth-century Archdiocese of Lima come to life here as perhaps the most revealing sources on colonial Andean religion and culture. Focusing on a largely neglected period, 1640 to 1750, and moving beyond portrayals that often view the relationships between indigenous peoples and Europeans solely in terms of repression, opposition, or accommodation, Kenneth Mills provides a wealth of new material and interpretation for understanding native Andeans and Spanish Christians as participants in a shared, if not harmonious, history. By examining colonial interaction and "religion as lived," he introduces memorable native Andean and Spanish actors and finds vivid points of entry into the complex realities of parish life in the mid-colonial Andes